UZBEK ROMANCE STUDIES IN THE INDEPENDENCE PERIOD: ISSUES OF ARTISTIC AND SCIENTIFIC THINKING (Scientific journal of the Fergana State University, 2023)
This article talks about the achievements of Uzbek novelists in the period of independence and the researches devoted to them. The first stage of Uzbek novels in the period of independence - 1990 - 2000, the magnificent novels of Amon Mukhtar, "Fields left by my father" by Togai Murad, "Lolazor" by Murad Mukhammed Dost, "Bazar" by Khurshid Dostmukhammed, Nazar Eshanqul's "Go‘roghli", Ulug‘bek Khamdam's "Equilibrium", Tokhtamurod Rustam's "Butterfly Game" and in the second stage - Naim Karimov's "Cholpon", , created from the 2000s until now Novels such as "The Wise Sisyphus" by Khurshid Dostmukhammad, "Bird in the Fano steppe" by Asad Dilmurod, "Free" by Isajon Sultan, and "God's Well" by Erkin Samandar are comparatively analyzed. Kh.Dostmukhammad's novels "Bazar" and "The Wise Sisyphus" are artistically interpreted in the novel thinking and represent the artistic and aesthetic thinking of the society, as well as the representation of the ancient Greek myth and the French writer Albert Camus's "Myth of Sisyphus". In the period of independence, the novels were created interpreted and analyzed by Uzbek novelists, such as Zulfiya Pardaeva, Yoldoshkhoja Solizhanov, Shoira Doniyorova, Islamjon Yakubov, Mubora Omonova, and the issues raised in them were also discussed.